Comparison of model free control strategies for chatter suppression by an inertial actuator. (30th October 2019) - Mancisidor, Iker; Pena-Sevillano, Alexander; Barcena, Rafael; Franco, Oier; Munoa, Jokin; Lacalle, Luis Norberto Lopez De
The employment of inertial active damping devices for chatter suppression in machining processes has been widely studied. The main drawback is that machine tools generally offer reduced spaces for the actuator location close to the cutting point and, hence, a reduced volume design is required for this external device. Consequently, the ratio between the force capability and the occupied volume is of major importance. Therefore, the performance of the actuator must be exploited to the fullest, which depends principally on the selected control strategy to determine the force to be exerted. The work presents the comparison of the most used feedback control algorithms and a novel strategy based on the regenerative effect disturbance. Their results are assessed for orthogonal cutting cases, with the aim of optimising the behaviour of the active damping system.